Uncommon Cause of Psychotic Behavior in a 9-Year-Old Girl: A Case Report - Willemina K. Van Putten; Said Hachimi-Idrissi; Anna Jansen; Viola Van Gorp; Luc Huyghens (Case Reports in Medicine)
Anti-N-methyl-D-aspartate receptors encephalitis (ANMDARE) is a well-defined, life threatening, but treatable disorder that often occurs as a paraneoplastic manifestation of ovarian teratomas in adult women. We report a child with this disorder who displayed a subacute onset of delirium, seizures, and autonomic instability. Antibodies against NMDA receptor were detectable in the serum and in the cerebrospinal fluid. No teratoma or other tumour was detected. We speculate that the previous viral/mycoplasma infection may be the trigger of this encephalitis. This patient showed a reversal of the neurological symptoms after intravenous immunoglobulin. Prompt recognition of this disorder followed by immunotherapy results in full neurological recovery.